Literary and Religious Texts. First Part - Gadd, Cyril J. (1963)
Publications of the Joint Expedition of the British Museum, and of the University Museum (University of Pennsylvania, Philadelphia) to Mesopotamia; Printed by order of the Trustees of the two Museums.